Economic Factors Driving Truck Drivers' Income: An Analysis of Working Hours, Service Fees, and Capital - Wettebosy, Rahmawati S.; Rahayu, Yuyun Puji; Aninam, Johny (Jurnal EMT KITA, 2026)
Energy resources play a crucial role in economic activities since nearly all human endeavors depend on energy sources like petroleum. This resource is essential for industrial, domestic, and transportation purposes. Problems emerge when some fuels receive subsidies while others do not. Nonetheless, the effect of the price disparity between subsidized and non-subsidized oil on the earnings of goods transport drivers remains ambiguous. This research intends to assess the impact of working hours, service pricing, and capital on the income of truck drivers in Manokwari Regency. This investigation employs a quantitative approach, drawing from both secondary and primary data, and utilizes multiple linear regression statistical methods for analysis. Findings from the multiple linear regression analysis indicate that working hours do not significantly influence truck driver income, whereas both service prices and capital do show a substantial impact on their income with p-value 0.003 and 0.072 consecutively. The analysis further reveals that, when considered together, working hours, service prices, and capital significantly affect the income of truck drivers at a 95% convidence level.